Toward an Integrative Model of Islamic Religious Education For Adolescent Self-Protection: a Systematic Review of Madrasah Contexts - Arif Rahmat Triasa (Fahmina: Jurnal Pendidikan Islam, 2026)
Adolescents in the digital era face increasingly complex moral, psychological, and digital risks, including cyberbullying, harmful online content, substance abuse, online gambling, and mental health problems, requiring self-protection capacities that extend beyond cognitive skills alone. Conventional educational approaches remain predominantly cognitive-behavioral and fragmented, often failing to address the holistic development needed to navigate these multidimensional challenges. Islamic Religious Education (PAI) in madrasah contexts offers a promising alternative by integrating moral values, spiritual formation, and psychosocial development into character education. In this review, adolescent self-protection is understood as the capacity to anticipate, avoid, manage, and recover from moral, psychological, social, and digital risks through moral self-regulation, emotional resilience, digital-ethical literacy, adaptive coping, and protective decision-making. This study aims to synthesize existing evidence on PAI-based strategies for adolescent self-protection and to develop an integrative conceptual model. Using a systematic literature review based on the PRISMA 2020 framework, fifty peer-reviewed journal articles published between 2017 and 2025 were selected through predefined inclusion and exclusion criteria and analyzed using thematic synthesis. The findings identify four interconnected dimensions of PAI-based self-protection: the internalization of Islamic moral values, transformative psycho-theological pedagogy, preventive and risk-responsive educational interventions, and ecological collaboration among schools, families, and communities. The review also highlights contextual factors and implementation barriers influencing these strategies. The study proposes an evidence-informed integrative model that positions Islamic Religious Education as a holistic and context-adaptive protective system for adolescent development in madrasah settings, while emphasizing the need for future empirical validation.